2022
DOI: 10.1017/s1537592722001050
|View full text |Cite
|
Sign up to set email alerts
|

Black Lives, White Kids: White Parenting Practices Following Black-Led Protests

Abstract: Summer 2020 saw widespread protests under the banner Black Lives Matter. Coupled with the global pandemic that kept America’s children in the predominant care of their parents, we argue that the latter half of 2020 offers a unique moment to consider whites’ race-focused parenting practices. We use Google Trends data and posts on public parenting Facebook pages to show that the remarkable levels of protest activity in summer 2020 served as a focusing event that not only directed Americans’ attention to racial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 88 publications
1
5
0
Order By: Relevance
“…All child-rearing happens within a specific political context -with some forces attempting to recreate and others challenging the existing social order (Parsons 2013). Within this context, adults must make choices about how they discuss political events with children (Orren and Peterson 1967) or even whether to introduce them to controversial issues, like race, at all (e.g., Anoll, Engelhardt, and Israel-Trummel 2022;Hagerman 2018;Sullivan, Eberhardt, and Roberts 2021). These choices take place within families but may also be legislated.…”
Section: Social Movements and Political Socializationmentioning
confidence: 99%
See 2 more Smart Citations
“…All child-rearing happens within a specific political context -with some forces attempting to recreate and others challenging the existing social order (Parsons 2013). Within this context, adults must make choices about how they discuss political events with children (Orren and Peterson 1967) or even whether to introduce them to controversial issues, like race, at all (e.g., Anoll, Engelhardt, and Israel-Trummel 2022;Hagerman 2018;Sullivan, Eberhardt, and Roberts 2021). These choices take place within families but may also be legislated.…”
Section: Social Movements and Political Socializationmentioning
confidence: 99%
“…In challenging existing social orders, sustained movements place new topics on the agenda, introduce novel information and frames, and can even update social norms (e.g., Gillion 2013;Giugni, McAdam, and Tilly 1999;Mendelberg 2001;Wasow 2020). In doing so, movements may call attention to crises and events that need to be interpreted for children (King, Schneer, and White 2017;Roberts, Wanta, and Dzwo 2002;Vu and Gehrau 2010), provide information for how to talk to kids about politics, or create new opportunities for children to engage (Anoll, Engelhardt, and Israel-Trummel 2022). Social movements, too, may introduce new social demands for raising "good" children that shape childrearing priorities (McAdam 1986).…”
Section: Social Movements and Political Socializationmentioning
confidence: 99%
See 1 more Smart Citation
“…The little research that has been done suggests that White parents may be more likely to emphasize racial discrimination and the challenges faced by people of color than the benefits of Whiteness (Abaid et al, 2022;Gilleen-O'Neel et al, 2022;Heberle et al, 2021). For example, in a study of White US parents' racial socialization practices conducted in the latter half of 2020, Anoll et al (2022) found that 79% of parents reported that they discussed the discrimination non-White individuals face, but only half said that they discussed White privilege with their children. Even among parents who take a color-conscious approach to racial socialization, few parents openly discuss Whiteness and White privilege, either in general or in relation to the parent's or child's own life (Abaied et al, 2022;Gillen-O'Neel et al, 2022;Heberle et al, 2021;Sullivan et al, 2021).…”
Section: Parental Racial Socialization In White Familiesmentioning
confidence: 99%
“…This is especially true for black sons, who receive more messages focused on stereotypes and structural barriers than their female counterparts (Lesane-Brown 2006;Stevenson et al 2005). In contrast, many white Americans see the carceral state as protecting and serving people like them, messages conveyed implicitly and explicitly to their children (Abaied and Perry 2021;Anoll, Engelhardt, and Israel-Trummel 2022;Sidanius and Pratto 1999).…”
Section: Information Attitudes and Direct Contact With State Agentsmentioning
confidence: 99%